Employment protection legislation in transition and emerging markets - Alexander Muravyev (IZA World of Labor, 2014)
Employment protection legislation aims to shield employees against unfair dismissal and earning reductions at the time of job loss. Theory suggests that employment protection stabilizes employment over cyclical upturns and downturns without necessarily increasing general unemployment. However, recent evidence from transition and emerging economies shows that employment protection legislation tends to raise unemployment among disadvantaged groups, particularly youth, and may increase informal work. Employment protection policies thus require careful consideration of their unintended effects.
Keywords: J68; K31; P20; 330; employment protection; unemployment; informality; transition and emerging economies